The In-deep Study Problems Organizers Inclusive Education of Medium School in Learning Science in Padang - Festiyed Festiyed; Mega Iswari (Journal of ICSAR, 2018)
This study aims to identify where the occurrence of bottlenecks in the science learning process of secondary school inclusive education providers for children with special needs (ABK), through deep study. Informants in this research are teachers who are involved in science learning in schools implementing inclusive education in Padang city. Data were collected by interview, observation and questionnaire method as the main method. Assistive methods in the form of documentation. Qualitative data analysis through 4 paths is data collection, data reduction, data display, draw a conclusion. The result of initial research of 102 schools SMA / MA / SMK in Padang city there are problems of interaction of six components of education process (curriculum, educator, learner, facilities and infrastructure, technology and learning media, assessment system). From 102 schools and there are 4 schools conducting inclusive education with 56 students spread in SMK Negeri 4 as many as 18 people, SMK Negeri 6 as many as 27 people, SMK Negeri 7 as many as 8 people, SMK Negeri 8 as many as 3 people. based on the problem which related to teachers, students, schools, communities, and government experienced problems in the implementation of inclusive education because ABK difficulty varies according to their needs. Science learning for ABK has not done well according to the needs, characteristics, and limits of ability possessed by children with special needs. The guidance model, not yet focused on non-adaptive behavior or deviant behavior before they conduct activities of individual learning activities program.